Design of highly active Ni catalysts supported on carbon nanofibers for the hydrolytic hydrogenation of cellobiose - Frecha, Esther; Remón, Javier; Torres, Daniel; Suelves, Isabel; Pinilla, José Luis (Frontiers in Chemistry, 2022)
The direct transformation of cellulose into sugar alcohols (one-pot conversion) over supported nickel catalysts represents an attractive chemical route for biomass valorization, allowing the use of subcritical water in the hydrolysis step. The effectiveness of this process is substantially conditioned by the hydrogenation ability of the catalyst, determined by design parameters such as the active phase loading and particle size. Herein, mechanistic insights into catalyst design to produce superior activity were outlined using the hydrolytic hydrogenation of cellobiose as a model reaction. Variations in the impregnation technique (precipitation in basic media, incipient wetness impregnation, and the use of colloidal-deposition approaches) endowed carbon-nanofiber-supported catalysts within a wide range of Ni crystal sizes (5.8–20.4 nm) and loadings (5–14 wt%). The link between the properties of these catalysts and their reactivity has been established using characterization techniques such as X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy, and inductively coupled plasma-optical emission spectroscopy (ICP-OES). A fair compromise was found between the Ni surface area (3.89 m2/g) and its resistance against oxidation for intermediate crystallite sizes (∼11.3 nm) loaded at 10.7 wt%, affording the hydrogenation of 81.2% cellobiose to sorbitol after 3 h reaction at 190°C and 4.0 MPa H2 (measured at room temperature). The facile oxidation of smaller Ni particle sizes impeded the use of highly dispersed catalysts to reduce the metal content requirements.